The Influence of Social Media Marketing and Electronic Word of Mouth on Brand Image and Purchase Intention with Ventela Shoe Products in Pekanbaru City - Farhan, Muhammad Farhan; Rahayu, Deny Danar; Pratiwi, Dian (Program Pascasarjana, Universitas Riau, 2024)
The rapid development of the fashion world has attracted a lot ofpublic attention, especially among teenagers who want to lookattractive. Shoes are one of the most famous fashion trends, asevidenced by the creation of various models and types of shoes sold onthe market. Therefore, shoe industry companies offer affordableprices, have a good brand image, and are able to provide satisfactionto consumers. This study was conducted to determine the influence ofsocial media marketing and electronic word of mouth on brand imageand purchase intention with ventela shoe products in pekanbaru city.The population in this study were all consumers who were interestedin making purchases on the Ventela shoe brand who were domiciled inPekanbaru City with a sample size of 100 people. The data collectiontechnique in this study used a questionnaire with a quantitativemethod. The analysis tool used in this study was Path Analysis usingthe SPSS 26 application. The results of the study showed that 1. SocialMedia Marketing had a positive and significant effect on Brand Image;2. electronic Word Of Mouth had a positive and significant effect onBrand Image; 3. Social Media Marketing had a positive and significanteffect on purchase intention; 4. electronic Word Of Mouth has apositive and significant effect on purchase intention; 5. Brand Imagehas a positive and significant effect on purchase intention; 6. BrandImage is able to mediate the influence of Social Media Marketing onpurchase intention; 7. Brand Image is able to mediate the influence ofelectronic Word Of Mouth on purchase intention